Brainstorm ebook The power and purpose of the teenage brain. - Siegel, Daniel J. (2014)
In this New York Times –bestselling book, Dr. Daniel Siegel shows parents how to turn one of the most challenging developmental periods in their children’s lives into one of the most rewarding. Between the ages of twelve and twenty-four, the brain changes in important and, at times, challenging ways. In Brainstorm , Dr. Daniel Siegel busts a number of commonly held myths about adolescence—for example, that it is merely a stage of “immaturity” filled with often “crazy” behavior. According to Siegel, during adolescence we learn vital skills, such as how to leave home and enter the larger world, connect deeply with others, and safely experiment and take risks. Drawing on important new research in the field of interpersonal neurobiology, Siegel explores exciting ways in which understanding how the brain functions can improve the lives of adolescents, making their relationships more fulfilling and less lonely and distressing on both sides of the generational divide.